2019
DOI: 10.1002/jcp.28975
|View full text |Cite
|
Sign up to set email alerts
|

SPTBN1 and cancer, which links?

Abstract: SPTBN1 is a dynamic intracellular nonpleckstrin homology-domain protein, functioning as a transforming growth factor-β signal transducing adapter protein which is necessary to form Smad3/Smad4 complex. Recently SPTBN1 is considered to be associated with many kinds of cancers. SPTBN1 expression and function differ between different tumor states or types. This review summarizes the recent advances in the expression patterns of SPTBN1 in cancers, and in understanding the mechanisms by which SPTBN1 affects the occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…To date, the changes of βII spectrin in clinical diseases cannot be ignored. As mentioned above, previous studies have also demonstrated that SPTBN1 was down-regulated in a variety of cancers, such as hepatocellular carcinoma, gastrointestinal tumors and lung cancer 10,30,69 . At the same time, its expression level is closely related to the patient's prognosis, such as hepatocellular carcinoma, pancreatic cancer and lung cancer 61,66,72,73,102 .…”
Section: The Potential Of βIi Spectrin (Sptbn1) As a Therapeutic Targetmentioning
confidence: 68%
See 2 more Smart Citations
“…To date, the changes of βII spectrin in clinical diseases cannot be ignored. As mentioned above, previous studies have also demonstrated that SPTBN1 was down-regulated in a variety of cancers, such as hepatocellular carcinoma, gastrointestinal tumors and lung cancer 10,30,69 . At the same time, its expression level is closely related to the patient's prognosis, such as hepatocellular carcinoma, pancreatic cancer and lung cancer 61,66,72,73,102 .…”
Section: The Potential Of βIi Spectrin (Sptbn1) As a Therapeutic Targetmentioning
confidence: 68%
“…Notably, the versatile role of βII spectrin in disease has been reported in an increasing numbers of studies, and βII spectrin has been implicated in diseases such as cancer, neurological disorders, cardiovascular diseases, osteoporosis, and hearing loss 2,[10][11][12][13] . Strikingly, growing evidence associates βII spectrin with various cancers, and expression and function vary between different tumor stages or types of βII spectrin 10 . Moreover, the most serious effect was observed in mice deficient in βII spectrin, which caused embryonic lethality 14 .…”
Section: Ivyspringmentioning
confidence: 99%
See 1 more Smart Citation
“…SPTBN1 can regulate the cell cycle and EMT through TGF-β and Wnt/β-catenin signaling pathways, thus regulating the proliferation and migration of hepatocellular carcinoma. In addition, SPTBN1 can play an anticancer role by regulating apoptosis, DNA damage repair and angiogenesis [31]. In EOC, it was reported that SPTBN1 contributed to platinum resistance by forming a spectrin-GS-pt complex [18].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to reanalyze an existing dataset in order to see if novel genes could be found. Microarray data analysis, filtering and feature selection revealed that COL10A1, SPOCK2, SPTBN1, RTKN2, FUT2 and AGER differentially expressed genes may be potentially involved in NSCLC and many other studies have demonstrated the same result [21][22][23][24][25][26][27]. COL10A1 [22] was identified to be common to all three algorithms, suggesting that it could be a gene that may play an important role in NSCLC.…”
Section: Discussionmentioning
confidence: 89%